Redefining Asian tourism. (April 2020) - Yang, Elaine Chiao Ling; Ong, Faith
Abstract: Research examining Asian tourism destinations and markets has burgeoned, paralleling the region's economic and middle-class growth. However, despite this burgeoning, extant studies tend to replicate theories and models from western tourism literature, with few attempts to interpret tourism from and in Asia through an indigenous lens. This editorial provides an overview of the current state of play in relation to past Asian tourism special issues, book publications and research articles as well as papers included in this special issue. Through the broad themes of deconstructing the universality of tourism knowledge, legitimising other ways of knowing, and convergence of knowledge, we borrow the lenses of research articles included in this special issue to critically examine colonised knowledge, offer alternative ways of conceptualising Asian tourism, and reflect on our journey of composing this special issue. Suggestions are provided for future researchers to take on this path of decolonising tourism knowledge. Highlights: Few studies of Asian tourism have engaged in local methodologies and epistemologies. There are unexplored layers of complexity in Asian tourism scholarship. The collection aims to decolonise tourism knowledge, legitimise other ways of knowing and promote convergence of knowledge.